Implementasi Augmented Reality Image Tracking Gandrung Traditional Dance Game of East Java to elevate Indonesian Culture - Oktaviana Tri Wulanndari; I Kadek Dwi Nuryana (Journal of Informatics and Computer Science (JINACS), 2023)
Abstrak— Banyak tradisi dan suku bangsa di Indonesia merupakan warisan budaya yang turun-temurun dilakukan oleh masyarakat, namun dampak globalisasi yang kuat telah mempengaruhi generasi muda yang kehilangan identitas dan pengetahuan tentang budaya mereka. Karya-karya leluhur terabaikan akibat digitalisasi yang merajalela. Salah satu contoh tari tradisional adalah "Gandrung" dari Banyuwangi, Jawa Timur, yang awalnya dibawakan oleh pemaju dan penari gandrung, tetapi kini lebih sering ditampilkan oleh perempuan. Undang-undang pemajuan kebudayaan mendorong penggunaan teknologi Augmented Reality (AR) untuk memperkenalkan tarian tradisional kepada masyarakat, namun kurangnya minat baca dan pemahaman terhadap budaya mengakibatkan sejarah dan makna tarian terlupakan. Penggunaan AR memungkinkan masyarakat untuk berinteraksi dengan objek virtual yang memberikan informasi tentang budaya daerah secara langsung. Pengembangan teknologi AR dalam aplikasi game kartu "Gandrung" diharapkan dapat berkontribusi dalam pelestarian budaya dan memberikan pengalaman edukatif yang berharga kepada masyarakat. Kata Kunci— Trandisi, Augmented reality, Gandrung, Teknologi, Tarian tradisional. Many traditions and ethnicities in Indonesia are cultural heritages that have been passed down through generations by the community, but the strong impact of globalization has influenced the younger generation, causing them to lose their identity and knowledge about their culture. Ancestor's works have been neglected due to the widespread digitization. One example of a traditional dance is "Gandrung" from Banyuwangi, East Java, which was originally performed by male performers and "penari gandrung" (Gandrung dancers), but now it is more commonly performed by women. The cultural advancement law encourages the use of Augmented Reality (AR) technology to introduce traditional dances to the community, but the lack of interest in reading and understanding culture has led to the forgetting of the history and significance of the dance. The use of AR allows people to interact with virtual objects that provide direct information about the local culture. The development of AR technology in the "Gandrung" card game application is expected to contribute to cultural preservation and provide valuable educational experiences to the community. Kata Kunci— Tradition, Augmented reality, Infatuation, Technology, Traditional dance.